Volume 3: Coal, Biomass and Alternative Fuels; Combustion and Fuels; Oil and Gas Applications 1989
DOI: 10.1115/89-gt-322
|View full text |Cite
|
Sign up to set email alerts
|

Ultra Low NOx Emissions for Gas and Liquid Fuels Using Radial Swirlers

Abstract: Curved blade radial swirlers using all the primary air were investigated with applications to lean burning gas turbine combustor primary zones with low NOx emissions. Two modes of fuel injection were compared, central and radial swirler pássage injection for gaseous and liquid fuels. Both fuel systems produced low NOx emissions but the upstream mixing in the swirler passages resulted in ultra low NOx emissions. A 140mm diameter atmospheric pressure combustor was used with 43% of the combustor air flow into the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…In order to characterize the Company DLE radial swirler, a derived geometrical swirl number S g [4,6] is employed to evaluate the strength of the rotational flow regime provided by the stabilizer. It can be used as a design tool to calculate specific designs of the radial swirler and combustion chamber.…”
Section: Swirl Numbermentioning
confidence: 99%
See 2 more Smart Citations
“…In order to characterize the Company DLE radial swirler, a derived geometrical swirl number S g [4,6] is employed to evaluate the strength of the rotational flow regime provided by the stabilizer. It can be used as a design tool to calculate specific designs of the radial swirler and combustion chamber.…”
Section: Swirl Numbermentioning
confidence: 99%
“…The investigation carried out by Andrews, Alkabie and co-workers [4][5][6][9][10][11][12][13][14][15][16] demonstrated that with more fuel holes located in the upstream region in the passages of the swirler and other stabilizing mechanisms, an improvement in the mixing process could be achieved. In this way more fuel-air uniformity could be achieved to eliminate any local rich zone that may cause a rise in local reaction temperature and hence more thermal NO x emission via the Zeldovich mechanism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This type of impingement cooled combustor design with most of the combustion air entering the head of the combustor is ideally suited to lean burning low NOx combustors and to high temperature rise combustors (Alkabie and Andrews, 1989). The type of combustor design envisaged is shown in Fig.l, where a pressure loss of 0.5% of the impingement wall and 3% of the combustor liner are typical pressure loss values.…”
Section: Nomenclaturementioning
confidence: 99%
“…This method of fuel injection was found to have a much better weak extinction but worse NOx emissions than for fuel injection in the vane passages or at the swirler periphery. These latter two fuel injection techniques have been shown to result in ultra low NOx characteristics whilst achieving a weak extinction much better than for premixed combustion (Alkabie and Andrews, 1988, 1989, 1990. The aim of the present work was to investigate whether central fuel injection could achieve lower NOx emissions, closer to those of the vane passage or peripheral fuel injection, without the relative poor flame stability of these modes of fuel injection.…”
Section: Introductionmentioning
confidence: 98%